Conjugated Linoleic Acid and Exercise may Share One Biochemical Pathway to Induce Fat-loss - Keizer,Hiskias G. (2013)
Conjugated linoleic acid is a functional ingredient which induces fat-loss in various high quality studies in humans. Although the effect is usually moderate in size, both in vitro studies with conjugated linoleic acid and studies on mice suggest that this effect is real and has a functional basis. Evidence, from in vitro studies and from studies in mice, shows that conjugated linoleic acid affects the expression of a number of genes or gene products which are involved in fat accumulation in adipose tissue. Based on scientific literature we hypothesize that these genes are part of an AMP-kinase dependent body composition regulating (ABC) network that functions both in adipocytes and muscle cells. This network may affect not only adipose tissue but also, lean body mass and exercise endurance and is probably also activated by doing exercise. The consequence of this model is that exposure to conjugated linoleic acid and exercise together may help to enhance fat-loss since they share a common biochemical pathway.